SI PEKA (Aksi Peduli Sisa Makanan) : Maggot sebagai Solusi Ramah Lingkungan - Pangestika, Zalma Niendya; Setyaputri, Nanda Aji; Pujiati, Amin; Melati, Inaya Sari (Universitas Pahlawan Tuanku Tambusai, 2025)
Organic waste management is a challenge in cities, including Bandar Lampung City. As the population increases, the volume of waste is increasing. So there is a need for further innovation in the environment through the SI PEKA program. One of the keys is to utilize Black Soldier Fly (BSF) maggots to manage waste from food waste. The maggot-based waste control model as an alternative to reduce waste while promising products with useful value. The purpose of this activity is to provide information on community empowerment in the use of waste from food waste. The methods used in community service include data collection, socialization, counseling, mentoring, monitoring, and evaluation. The results of this activity are increased knowledge, skills of the GenBI community in managing household waste for maggot cultivation, participation in supporting and utilizing waste as environmentally friendly solutions, and supporting the circular economy into useful products.